Cases report: MRI findings of asymptomatically familial subependymal heterotopia with filamin A gene abnormality - Lv, Bin; Zhou, Yushan; Zeng, Jianguang; Wang, Ling; Zhao, Fumin; Chen, Huizhu; Li, Xuesheng; Song, Yu; Xiao, Mei; Ding, Zhiyong; Cheng, Bochao (Frontiers in Neuroscience, 2022)
Subependymal heterotopia (SEH) is a rare neuronal migration disorder consisting of gray matter nodules along the lateral ventricular walls and often associated with other brain malformations. Despite most SEH cases showing epilepsy during their lifetimes, very few patients with asymptomatically familial SEH tend to cause misdiagnosis or missed diagnosis. We present four familial SEH cases without any positive symptoms and medical history, including two fetus, who were diagnosed by magnetic resonance imaging (MRI) and confirmed by genetic testing with mutation of filamin A. This report emphasizes the role of MRI in recognition of SEH at an early age of gestation and in asymptomatically familial SEH. MRI provides a fast, repeatable, reliable, and cheap choice for detecting and screening familial SEH.